Chemical evaluation and anticholinesterase activity of Hippeastrum puniceum (Lam.) Kuntz bulbs (Amaryllidaceae) - Letícia Carlesso Soprani; Jean P. de Andrade; Vanessa Dias dos Santos; Anderson Alves-Araújo; Jaume Bastida; Cristian A. Gasca Silva; Damaris Silveira; Warley de Souza Borges; Claudia Masrouah Jamal (Universidade de São Paulo, 2021)
Hippeastrum puniceum is a species that belongs to the Amaryllidaceae family. A particular characteristic of this family is the consistent and very specific presence of isoquinoline alkaloids, which have demonstrated a wide range of biological activities such as antioxidant, antiviral, antifungal, antiparasitic, and acetylcholinesterase inhibitory activity, among others. In the present work, fifteen alkaloids were identified from the bulbs of Hippeastrum puniceum (Lam.) Kuntz using a GC-MS approach. The alkaloids 9-O-demethyllycoramine, 9-demethyl-2α-hydroxyhomolycorine, lycorine and tazettine were isolated through chromatographic techniques. The typical Amaryllidaceae alkaloids lycorine and tazettine, along with the crude and ethyl acetate extract from bulbs of the species were evaluated for their inhibitory potential on α-amylase, α-glucosidase, tyrosinase and acetylcholinesterase activity. Although no significant inhibition activity was observed against α-amylase, α-glucosidase and tyrosinase from the tested samples, the crude and ethyl acetate extracts showed remarkable acetylcholinesterase inhibitory activity. The biological activity results that correlated to the alkaloid chemical profile by GC-MS are discussed herein. Therefore, this study contributed to the knowledge of the chemical and biological properties of Hippeastrum puniceum (Lam.) and can subsidize future studies of this species.